Iowa Birdline update, February 6, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for February 6, 1989. Severe weather largely shut down birding activity. Highlights for the week include sightings of Purple Finches, Lapland Longspurs and Harris' Sparrows. Epson - sheet feed/flatbed